Sustainable development in the BRICS countries: an efficiency analysis by data envelopment - Santana, Naja Brandao; Nascimento Rebelatto, Daisy Aparecida do; Périco, Ana Elisa [UNESP]; Mariano, Enzo Barberio [UNESP] (Taylor & Francis Inc, 2014)
There is much concern about the social and environmental impacts caused by the economic growth of nations. Thus, to evaluate the socio-economic performance of nations, economists have increasingly addressed matters related to social welfare and the environment. It is within the scope of this context that this work discusses the performance of countries in the BRICS group regarding sustainable development. The objective of this study regards evaluating the efficiency of these countries in transforming productive resources and technological innovation into sustainable development. The proposed objective was achieved by using econometric tools as well as the data envelopment analysis method to then create economic, environmental, and social efficiency rankings for the BRICS countries, which enabled to carry out comparative analyses on the sustainable development of those countries. The results of such assessments can be of interest for more specific scientific explorations.
Keywords: BRICS; data envelopment analysis; economic growth; efficiency; sustainable development